Valuing vulnerable geometric Asian options. (January 2016) - Jeon, Junkee; Yoon, Ji-Hun; Kang, Myungjoo
Abstract: An option on a defaultable instrument is prone to default risk arising from the probability that the instrument's issuer will not honor its contractual obligations. Under this financial circumstance, we consider vulnerable Asian options. In this paper, we obtain parabolic partial differential equations with time-dependent coefficients on the vulnerable Asian option model and derive a closed formula of the pricing of the vulnerable geometric Asian option using the pricing formula of the vulnerable European option with time-dependent coefficients.